Status Penyebaran Penyakit Tungro pada Padi di Jawa Barat - I Nyoman Widiarta; Yulianto Yulianto; M. Muhsin (Jurnal Perlindungan Tanaman Indonesia, 1997)
An investigation on the status of tungro virus was conducted in the coastal lowland paddy fields less than 100 m above sea level, in Bekasi, Karawang, Subang, lndramayu, Cirebon and highland paddy fields more than 100 m to 1500 m above sea level in Subang, Bandung, Purwakarta, Cianjur, Sukabumi, Bogor of West Java in wet season crop 1996/1997 to discover recent status of tungro virus disease infestation. Disease incidence was observed randomly from 100 hills in each locality. Leaves of rice plant were also sampled from each observation field for ELISA test in the laboratory. Population density and species composition of green leafhopper were observed from 25 single stroke sweeping net. Tungro symptom as well as virus were not discovered in the coastal lowland paddy fields. Therefore, the coastal lowland paddy fields were declared still uninfected by tungro virus until recently. However, the disease symptom and virus were observed in highland. The green leafhopper species Nephotettix virescens was dominant in both lowland and highland. The species N. nigropictus was only identified from highland paddy fields. Population density of green leafhopper was higher in highland than in lowland. Factors contributing to the different in population density and change in the species composition were discussed.